New taxa of the genus Phlugiolopsis (Orthoptera: Tettigoniidae: Meconematinae) from Yunnan, China, with comments on the importance to taxonomy of the left tegmen - Bian, Xun; Shi, Fuming (Zootaxa, 2018)
The relationships among the Phlugiolopsis species are poorly understood. In this paper, three new subgenera are proposed and four new species are described from Yunnan, China. The microstructures of male stridulatory files are examined for selected species of Phlugiolopsis using scanning electron micrographs (SEM). Geometric morphometric study of the left tegmen for the genus Phlugiolopsis was carried out to demonstrate the effect of vicariance on species. Differences among species are minute, suggesting that the separation is recent. All examined specimens are deposited in the Museum of Hebei University (HBUM).